2009
DOI: 10.1097/fjc.0b013e3181af04e5
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed and Cardiovascular Health

Abstract: Flaxseed and its components may improve cardiovascular health because of their numerous attributes. Flaxseed contains 35% of its mass as oil, of which 55% is alpha-linolenic acid (ALA). Flax meal, which is devoid of oil, contains the lignan secoisolariciresinol diglucoside (SDG). Flaxseed, flaxseed with very low ALA, flaxseed oil, flax lignan complex (FLC), and SDG reduce the development of hypercholesterolemic atherosclerosis by 46%, 69%, 0%, 73%, and 34%, respectively, in the rabbit model. FLC and SDG slow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 89 publications
0
94
1
8
Order By: Relevance
“…However, as stated in a recent review by Prasad, suppression of atherosclerosis by fl axseed is likely more attributable to the lignan content of fl axseed rather than ALA ( 14 ). It still remains unclear whether ALA, per se, may be benefi cial in atheroprotection by exhibiting cardioprotective properties similar to those observed with dietary EPA and DHA from fi sh oil.…”
Section: Quantifi Cation Of Mrna Levelsmentioning
confidence: 88%
“…However, as stated in a recent review by Prasad, suppression of atherosclerosis by fl axseed is likely more attributable to the lignan content of fl axseed rather than ALA ( 14 ). It still remains unclear whether ALA, per se, may be benefi cial in atheroprotection by exhibiting cardioprotective properties similar to those observed with dietary EPA and DHA from fi sh oil.…”
Section: Quantifi Cation Of Mrna Levelsmentioning
confidence: 88%
“…Subpopulations with higher consumption of lignans display considerable lower disease frequency [7,[15][16][17][18][19][20][21][22]. In several studies, lignan-rich foods, concentrates or partially purified compounds have been shown to improve blood lipids, to enhance glycemic control and to alleviate or cure type 1 and type 2 diabetes [23][24][25][26][27]. However, the results produced in these studies, although very promising, were not homogeneous due to their different and often fragmented approaches.…”
Section: Introductionmentioning
confidence: 99%
“…SDG reduced the angiotensin I-induced rise in the arterial pressures and hence SDG was a potent Angiotensin-Converting Enzyme (ACE) inhibitor (Paschos et al, 2007;Prasad, 2009). And SDG supplementation could protect against the development of chronic diseases, cancer and diabetes on animal studies using various models of rat, mice and rabbit (Adolphe et al, 2010).…”
Section: The Statistical Analysismentioning
confidence: 99%